Comportamento mecânico da coluna vertebral durante uma corrida de longa distância - Silva, Gyan Gomes da (2021)
The description of the mechanical behavior of the spine during a long distance run can assist in the periodization of training loads and in the prevention of injuries related to the lumbar spine, based on the consequences of the mechanical stress imposed on the spine during the run. Thus, the objective of the present work was to describe the mechanical behavior of the spine during a long distance run. Height variation, peak torque of the flexor and extensor muscles of the trunk and the level of neuromuscular activation of the upper abdominais rectus URA, lower abdominis rectus LAR, external oblique EO, longissimus LON and iliocostalis ILIOC were quantified. Seventeen male runners participated in this research, aged 38.4 years ± 7.3 years, body mass index BMI of 22.8 ± 2.2, practice time of 10.8 years ± 6.1 years . There was a reduction in height throughout the race, being significant (p < 0.05), in the comparisons between the tests performed at the beginning vs 14, 21, and 28 km, 7 km vs 21 and 28 km and 14 km vs 28 km. The peak torque PT of the trunk flexor muscles showed a significant reduction (p < 0.05) in the comparisons between the tests performed at the beginning vs 7, 14, 21 and 28 km and 7 km vs 21 and 28 km, different from the PT of the trunk extensor muscles, where there was a significant reduction (p < 0.05) only between comparisons between the beginning vs 21 and 28 km. Regarding the electromyographic behavior, the UAR and LAR muscles showed significant reductions (p <0.05) only between the beginning x 28 km, the EO muscle between beginning vs 21 and 28 km and between 7 km vs 28 km, the LON muscle between beginning vs 21 and 28 km, and 7 km vs 21 and 28 km and the ILIOC muscle between beginning vs 14, 21 and 28 km and between 7 km vs 28 km. It is concluded that over 28 km of running, the variables responsible for sustaining overload of the spine were significantly impacted, and the present study made it possible to identify the critical moments where this occurred.